An approach to Measure Transition Density of Binary Sequences for X-filling based Test Pattern Generator in Scan based Design - Sabir Hussain; V. Malleshwara Rao (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Switching activity and Transition density computation is an essential stage for dynamic power estimation and testing time reduction. The study of switching activity, transition densities and weighted switching activities of pseudo random binary sequences generated by Linear Feedback shift registers and Feed Forward shift registers plays a crucial role in design approaches of Built-In Self Test, cryptosystems, secure scan designs and other applications. This paper proposed an approach to find transition densities, which plays an important role in choosing of test pattern generator We have analyze conventional and proposed designs using our approache, This work also describes the testing time of benchmark circuits. The outcome of this paper is presented in the form of algorithm, theorems with proofs and analyses table which strongly support the same. The proposed algorithm reduces switching activity and testing time up to 51.56% and 84.61% respectively.